Primary Hydatid Cyst of the Thyroid Gland - Azendour, Imen (Hindawi Publishing Corporation, 2011)
Primary hydatid cyst of thyroid gland is an exceptional localization even in Morocco where echinococcal disease is endemic. A 23-year-old woman presented with multiples cystic lesions of the thyroid revealed by neck mass and dyspnea. She underwent a subtotal thyroidectomy. The diagnosis of hydatid cyst was made preoperatively and was confirmed by histological studies. Further investigation failed to identify any other evidence of systemic hydatidosis. The patient has remained asymptomatic for 24 months after surgery. The possibility of hydatid disease, though rare, should be always kept in mind, for patients with cystic lesions of the thyroid, because a needle aspiration biopsy is a potentially harmful procedure.